Dependence of neoclassical toroidal viscosity on the poloidal spectrum of applied nonaxisymmetric fields. (5th February 2016) - Logan, N.C.; Park, J.-K.; Paz-Soldan, C.; Lanctot, M.J.; Smith, S.P.; Burrell, K.H.
Abstract: This paper presents a single mode model that accurately predicts the coupling of applied nonaxisymmetric fields to the plasma response that induces neoclassical toroidal viscosity (NTV) torque in DIII-D H-mode plasmas. The torque is measured and modeled to have a sinusoidal dependence on the relative phase of multiple nonaxisymmetric field sources, including a minimum in which large amounts of nonaxisymmetric drive is decoupled from the NTV torque. This corresponds to the coupling and decoupling of the applied field to a NTV-driving mode spectrum. Modeling using the perturbed equilibrium nonambipolar transport (PENT) code confirms an effective single mode coupling between the applied field and the resultant torque, despite its inherent nonlinearity. The coupling to the NTV mode is shown to have a similar dependence on the relative phasing as that of the IPEC dominant mode, providing a physical basis for the efficacy of this linear metric in predicting error field correction optima in NTV dominated regimes.